Bioremediation by Cupriavidus metallidurans Strain MSR33 of Mercury-Polluted Agricultural Soil in a Rotary Drum Bioreactor and Its Effects on Nitrogen Cycle Microorganisms - Guillermo Bravo; Paulina Vega-Celedón; Juan Carlos Gentina; Michael Seeger (Microorganisms, 2020)
Nitrogen cycle microorganisms are essential in agricultural soils and may be affected by mercury pollution. The aims of this study are to evaluate the bioremediation of mercury-polluted agricultural soil using Cupriavidus metallidurans MSR33 in a rotary drum bioreactor (RDB) and to characterize the effects of mercury pollution and bioremediation on nitrogen cycle microorganisms. An agricultural soil was contaminated with mercury (II) (20–30 ppm) and subjected to bioremediation using strain MSR33 in a custom-made RDB. The effects of mercury and bioremediation on nitrogen cycle microorganisms were studied by qPCR. Bioremediation in the RDB removed 82% mercury. MSR33 cell concentrations, thioglycolate, and mercury concentrations influence mercury removal. Mercury pollution strongly decreased nitrogen-fixing and nitrifying bacterial communities in agricultural soils. Notably, after soil bioremediation process nitrogen-fixing and nitrifying bacteria significantly increased. Diverse mercury-tolerant strains were isolated from the bioremediated soil. The isolates Glutamicibacter sp. SB1a, Brevundimonas sp. SB3b, and Ochrobactrum sp. SB4b possessed the merG gene associated with the plasmid pTP6, suggesting the horizontal transfer of this plasmid to native gram-positive and gram-negative bacteria. Bioremediation by strain MSR33 in an RDB is an attractive and innovative technology for the clean-up of mercury-polluted agricultural soils and the recovery of nitrogen cycle microbial communities.